ICTUSCOG: Poststroke cognitive impairment following nondisabling stroke: Study protocol of a spanish multicentre prospective cohort study - Cristina Moreno-Loscertales; Paula Canasto-Jiménez; Mario Bautista-Lacambra; Marta Serrano-Ponz; Isabel Campello-Morer; Marta Palacín-Larroy; Herbert Tejada-Meza; Esther Sierra-Martínez; Jorge Navarro López; Fidel Alfaro-Almagro; Gonzalo Forno-Martinic; Miguel Ángel Marín-Cárdenas; et al. (PLoS ONE, 2025)
Background Stroke is a leading cause of death and disability globally, with frequent cognitive sequelae affecting up to 60% of stroke survivors. Despite the high prevalence of post-stroke cognitive impairment (PSCI), early detection remains underemphasized in clinical practice, with limited focus on broader neuropsychological and affective symptoms. Stroke elevates dementia risk and may act as a trigger for progressive neurodegenerative diseases. However, the underlying neurobiological mechanisms and the interaction between vascular and degenerative pathways are poorly understood. The ICTUSCOG study aims to address these gaps by determining the incidence, predictors and progression factors of PSCI in a prospective, multicenter cohort of nondisabling stroke patients. The work will explore distinct patient profiles, evaluate the role of biomarkers, and develop a predictive model to identify at risk individuals. Methods ICTUSCOG is a five-year observational project involving four Spanish centres. Recruitment began in 2022 and includes consecutive patients aged 18–75 with no prior cognitive impairment and nondisabling stroke. Participants undergo detailed neuropsychological, functional, and neuroimaging assessments at baseline, 3, 6, and 12 months, and annually thereafter. Key data include stroke characteristics, vascular risk factors, advanced neuroimaging metrics, and biological biomarkers. Neuropsychological assessments incorporate domain-specific validated tools tailored for stroke patients. Discussion The study will quantify the incidence of early and late PSCI, identify predictors of progression, and characterise cognitive profiles. Multivariate models and clustering techniques will explore interactions among clinical, biological and imaging data. A predictive model will be developed and validated for clinical use. ICTUSCOG will provide critical insights into the mechanisms and trajectories of PSCI, informing prevention, early intervention, and rehabilitation strategies. The work aims to establish predictive tools and care pathways to mitigate the burden of cognitive impairment in stroke survivors.